Development on the leading small and medium-sized industry (SMI): food industry in Jambi Province - Sesraria Yuvanda; M. Rachmad R.; Zamzami Zamzami; M. Safri (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
The objectives of this research are: 1). to analyze the factors which determine the production of leading small-medium food industry, 2). to analyze the effect of leading small-medium food industry production towards community income. The analysis models used are simultaneous equation model (ESM) and simple regression. The research results show that the determining factors on the production of leading small-medium food industry are investment, production capacity, labor, sales, and the utilization of technology simultaneously. However, individually, the sales have significant influence on the production of leading small-medium food industry in which determined by promotion and market share. In addition, the influence of leading small-medium food industry is very significant on community income with a contribution of 59.54%. The amount of public income in the leading small-medium food industry is IDR 1.5 million for a single production period of 1.5 months or approximately IDR 1 million per month.